Habituation to Pain in "Medication Overuse Headache": A CO2 Laser-Evoked Potential Study - Ferraro, Diana; Vollono, Catello; Miliucci, Roberto; Virdis, Daniela; De Armas, Liala; Pazzaglia, Costanza; Le Pera, Domenica; Tarantino, Samuela; Balestri, Martina; Di Trapani, Girolamo; Valeriani, Massimiliano (Headache, 2012)
(Headache 2012;52:792‐807) Objective.— Our aim was to investigate CO2 laser‐evoked potential (LEP) habituation to experimental pain in a group of patients affected by medication‐overuse headache, with a history of episodic migraine becoming chronic, before and after treatment, consisting in acute medication withdrawal and a preventive treatment cycle. Background.— One of the main features of LEPs in migraineurs is a lower habituation to repetitive noxious stimuli during the interictal phase. Methods.— LEPs were recorded to stimulation of both the right hand and the right perioral region in 14 patients and in 14 healthy subjects. The habituation of both the N1 and the vertex N2/P2 components was assessed by measuring the LEP amplitude changes across 3 consecutive repetitions of 30 trials each. Results.— In the 8 patients who had clinically improved after treatment, the N2/P2 amplitude habituation was significantly higher after treatment than before treatment following both hand (F = 43.2, P < .0001) and face stimulation (F = 6.9, P = .01). In these patients, the N2/P2 amplitude habituation after treatment was not different from that obtained in healthy controls (P = .18 and P = .73 for hand and face stimulation, respectively). On the contrary, in the patients who did not improve, the N2/P2 amplitude still showed reduced habituation after both hand (F = 3.1, P = .08) and face (F = 0.7, P = .4) stimulation. Conclusion.— The deficient habituation of the vertex N2/P2 complex was partly restored after successful treatment of medication‐overuse headache, reflecting a modification in pain‐processing pathways.